Epigenomics and Schizophrenia: A Literature Review - Nishikant Thorat; Soham Kulkarni (BJPsych Open, 2025)
Aims: Schizophrenia is a severe mental illness, characterized by positive, negative, cognitive, affective symptoms with aggression, marked by disrupted structural and functional brain connectivity, as evidenced by neuroimaging, neurophysiological and neuropathological studies. Recent epigenetic research highlights the role of deoxyribonucleic acid (DNA) methylation, histone modifications, and non-coding ribonucleic acid (RNA) amongst others in mediating both genetic predisposition and environmental influences on gene expression as seen in schizophrenia.